Medicinal Properties of Flavonoids - Muheisen, Hassan Mahmoud; Ali, Israa Muhammad (Journal of medical and pharmaceutical sciences, 2019)
Flavonoids are ubiquitous in photosynthesizing cells and are commonly found in fruit, vegetables, nuts, seeds, stems, flowers, tea, and honey. Therefore, a significant quantity is consumed in our daily diet. These flavonoids are variously associated with the sensory and nutritional quality of our plant foods. For centuries, preparations containing these compounds as the principal physiologically active constituents have been used to treat human diseases. There has been increasing interest in the research on flavonoids from plant sources because of their versatile health benefits reported in various epidemiological studies. Since flavonoids are directly associated with human dietary ingredients and health, there is need to evaluate structure and function relationship. There have been many bioassay guided searches for cytotoxic antitumour agents in plants especially those known to be used in folk medicine for this purpose. This has led to the isolation and identification of quite a large number of active constituents from all the different flavonoid classes, e.g. catechins, flavans, dihydrochalcones, chalcones, flavanones, dihydro-flavonols, flavones, biflavonoids and flavonol. The purpose of the present review is to discuss recent developments in the biochemistry and medicinal aspects of the flavonoids. Flavonoids have received a lot of interest in scientific research over the past 20 years and have had many beneficial and potential effects. Flavonoids have many great advantages as natural compounds compared to therapeutic agents because many diets are rich in polyphenols and are consumed daily and are easily absorbed in the intestines after ingestion, especially flavonoids, have positive effects on health: antioxidants, lethargy, allergies and bacteria, And cancer. The protective effect of flavonoids is primarily due to its antioxidant effect and inhibition of enzymes. The protective effect of flavonoids from diseases is mainly due to their antioxidant effect. Recent research on the biological properties of flavonoids will therefore be a further subject of the present review.